Role of Calpain-1 in Neurogenesis - Baudry, Michel; Su, Wenyue; Seinfeld, Jeffrey; Sun, Jiandong; Bi, Xiaoning (Frontiers in Molecular Biosciences, 2021)
While calpains have been implicated in neurogenesis for a long time, there is still little information regarding the specific contributions of various isoforms in this process. We took advantage of the availability of mutant mice with complete deletion of calpain-1 to analyze its contribution to neurogenesis. We first used the incorporation of BrdU in newly-generated cells in the subgranular zone of the dentate gyrus to determine the role of calpain-1 deletion in neuronal proliferation. Our results showed that the lack of calpain-1 decreased the rate of neuronal proliferation in adult hippocampus. As previously shown, it also decreased the long-term survival of newly-generated neurons. We also used data from previously reported RNA and miRNA sequencing analyses to identify differentially expressed genes in brain of calpain-1 knock-out mice related to cell division, cell migration, cell proliferation and cell survival. A number of differentially expressed genes were identified, which could play a significant role in the changes in neurogenesis in calpain-1 knock out mice. The results provide new information regarding the role of calpain-1 in neurogenesis and have implications for better understanding the pathologies associated with calpain-1 mutations in humans.